Perancangan Aplikasi Penukaran Mata Uang Pada Dolarindo Money Changer - Sulistiyah, Sulistiyah; Farabi, Nur Ali; Susanti, Susanti; Fadholi , Arief; Rosmiati, Mia (POLITEKNIK NEGERI JAKARTA, 2023)
Money Changer is a business that operates in the foreign exchange market. Where one type of trade or transaction is buying and selling foreign currency. There are several problems with Dolarindo Money Changer, namely the currency exchange transaction system is still done manually so it takes quite a long time for Tellers or customers to find out information on the amount of foreign currency available, and also to find out the latest information about selling prices and buying prices for foreign currency. Customers and Tellers need media that can provide the information they need quickly and accurately. Data management that is still manual also results in a lot of data being lost and takes quite a long time to create reports. The aim of this research is to design a website-based money changer application that is able to meet company and customer needs. The currency exchange application on Dolarindo Money Changer is expected to be able to meet needs and be a solution to existing problems. This application was designed using the waterfall method by carrying out the stages in the waterfall method, namely design and analysis, system and program design, implementation, integration and testing, and finally maintenance. The application that has been designed can record and check foreign currency or foreign exchange stocks quickly and accurately. The existence of this website-based currency exchange application makes it easier and improves Teller performance in managing customer data, managing foreign exchange data, managing foreign exchange request data, and also creating foreign exchange reports.